Dance and Its Effect on the Mental Health of Performing Arts Students - Calica, Christian Ashley; Lobo, Joseph (Journal of Humanities and Social Sciences (JHASS), 2022)
This study is aimed to describe dance's effect and its different forms on mental health. The respondents of this study are students taking Bachelor of Performing Arts at City College of Angeles. The Mental Effect of Dance Questionnaire was utilized to gather data through an online survey. The said questionnaire has undergone pilot testing α =.975 and .946, which confirms that the instrument can be utilized. Descriptive analyses were used to describe the effects of dance and its different forms on mental health. Independent T-Test Analysis, Mann-Whitney U, and Kruskal-Wallis H analyses were utilized to determine the difference between groups in the cognitive effect of the dance and its genre regarding gender and year level. After data were obtained from 83 students, the results showed that dance positively affects their mental health. On the other hand, there was no significant difference between groups regarding gender and year level regarding the mental effect of the dance and its genres. Results found that most BPeA students answered that dance has a good impact and benefits them, especially in their mental health. From the results obtained, this study suggests providing different seminars and exposures for the students to gain knowledge about the benefits of dance based on various dance forms to students' mental health. These findings provide new information to students and professionals interested in researching dance and mental health. Further investigation is also recommended to support this research study.